Peter, Paul, and Mary Magdalene : the followers of Jesus in history and legend - Ehrman, Bart D. (Oxford ; New York : Oxford University Press, 2006)
From the Publisher: Bart Ehrman, author of the bestsellers Misquoting Jesus and Truth and Fiction in The Da Vinci Code, here takes readers on another engaging tour of the early Christian church, illuminating the lives of three of Jesus' most intriguing followers: Simon Peter, Paul of Tarsus, and Mary Magdalene.
Preface -- Introduction -- Part 1: Simon Peter -- 1: Quarry: our sources for Peter the rock -- 2: Peter: solid rock or shifting sand? -- 3: Rocky beginning -- 4: Peter at the Passion -- 5: On this rock I will build my church -- 6: Peter: Christian author and martyr -- Part 2: Apostle Paul -- 7: Apostle Paul: polling our sources -- 8: Paul the convert -- 9: Paul the apostle -- 10: Paul's proclamation according to later sources -- 11: Paul's impassioned allies -- 12: Paul's embittered enemies -- Part 3: Mary Magdalene -- 13: Mary Magdalene in popular culture and history -- 14: Mary during the ministry of Jesus -- 15: Jesus and Mary in conversation -- 16: Mary at the Passion -- 17: Mary and her revelations -- 18: Mary: the residual questions -- Conclusion: Peter, Paul, and Mary in perspective -- Notes -- Credits and permissions -- Index.
Includes bibliographical references (pages 261-272) and index.
Print version record.
Master record variable field(s) change: 050, 082
Keywords: Peter, -- the Apostle, Saint; Paul, -- the Apostle, Saint; Mary Magdalene, -- Saint; Mary Magdalene, -- Saint; Paul, -- the Apostle, Saint; Peter, -- the Apostle, Saint; Bibel; Brown, Dan; Maria Magdalena; RELIGION -- Biblical Biography -- New Testament; Historiciteit; Mythen; Vroege christendom; Rezeption; Electronic books